A Pelatihan Penilaian Status Gizi Anak Sebagai Upaya Pencegahan Gangguan Gizi Pada Anak Disusun 3 Desa Srikuncorosia: - Desi Lastari; Echi Rianchi; Samidah, Ida (Gayaku Publisher, 2024)
This training aims to describe the assessment of children's nutritional status as an effort to prevent nutritional disorders in parents of children under 12 years of age in hamlet 3 of Srikuncoro village, Central Bengkulu district. Based on observations, there are still parents who do not understand how to assess their child's nutritional status. In fact, assessing children's nutritional status is important for preventing nutritional disorders in their children in order to avoid nutritional problems so that children's health is always maintained. It is not only Hamlet 3, Srikuncoro village, Central Bengkulu district that does not understand this nutritional status assessment, in fact throughout Indonesia there are still many parents who do not understand the nutritional status assessment of their own children. There have been many cases of nutritional problems in children under 12 years of age, therefore training was held on assessing the nutritional status of children in Hamlet 3.